Manajemen Mutu Pembelajaran Al-Qur’an Berbasis Metode Qiro’at Marhalah Dalam Meningkatkan Kualitas Bacaan Santri (Study Kasus Di Pondok Pesantren Al-Qur’an Al-Falah 2 Nagreg Bandung) - Riki Andhika; Dr. Imaduddin (Journal of Innovative and Creativity, 2025)
This research examines the Quality Management of Al-Qur'an Learning Using the Qiroa't Marhalah Method. Analysts should also know that Qiro'at Marhalah's strategy is to provide a way for students to read the Koran well in Al-Falah 2 Nagreg. Quality management is an effort to manage the management of an organization as a whole to achieve superior performance in all aspects of a product or service. Nowadays, we often find people or Islamic boarding school institutions who read the Koran poorly. According to Muslim beliefs, the Koran is the first and foremost source or guide to Islamic teachings and its truth has been acknowledged. The Qiro'at Marhalah method is available to solve the shortcomings of every reader to read the Quran better.